2010
DOI: 10.1007/s11011-010-9215-9
|View full text |Cite
|
Sign up to set email alerts
|

Creatine prevents the inhibition of energy metabolism and lipid peroxidation in rats subjected to GAA administration

Abstract: Guanidinoacetate methyltransferase (GAMT) deficiency is an inherited neurometabolic disorder, biochemically characterized by the tissue accumulation of guanidinoacetate (GAA). Affected patients present epilepsy and mental retardation whose etiopathogeny is unclear. Previous reports have shown that GAA alters brain energy metabolism and that creatine, which is depleted in patients with GAMT deficiency, can act as a neuroprotector; as such, in the present study we investigated the effect of creatine administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In the striatum of rats, GAA probably interferes with energetic metabolism at the level of complex II, ATPase and creatine kinase activities through lipid peroxidation causing oxidative stress (Zugno et al., 2006; Zugno et al, 2007). Creatine prevents the neurotoxicity of GAA in rat striatum (Kolling & Wyse, 2010). Moreover, GAA (but not creatine) has a specific mimetic effect on GABA A receptors (Neu et al., 2002).…”
Section: Pathogenetic and Physiopathologic Aspectsmentioning
confidence: 99%
“…In the striatum of rats, GAA probably interferes with energetic metabolism at the level of complex II, ATPase and creatine kinase activities through lipid peroxidation causing oxidative stress (Zugno et al., 2006; Zugno et al, 2007). Creatine prevents the neurotoxicity of GAA in rat striatum (Kolling & Wyse, 2010). Moreover, GAA (but not creatine) has a specific mimetic effect on GABA A receptors (Neu et al., 2002).…”
Section: Pathogenetic and Physiopathologic Aspectsmentioning
confidence: 99%
“…Arginine is a substrate for the enzyme arginine-glycine amidinotransferase (AGAT), which forms guanidinoacetate (GAA) and ornithine from glycine and arginine (Schulze and Battini 2008). GAA enhances oxidative stress in the rat brain (Zugno et al 2008) and these changes have been hypothesized to contribute to the central nervous system (CNS) pathophysiology in guanidinoacetate:methyltransferase (GAMT) deficiency (Amayreh et al 2014;Grioni et al 2014;Kolling and Wyse 2010). It has been suggested that elevated plasma GAA contributes to neuropathology in ARG1 deficiency (Amayreh et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Creatine solution (50 mg/kg of body weight) was injected intraperitoneally, once a day, from the 6th to the 28th days of age . Control animals received saline solution in the same volumes as those applied to Hcy‐treated and creatine‐treated rats.…”
Section: Methodsmentioning
confidence: 99%